Employee Performance in Relation to Work Environment and Discipline: Evidence from the Deli Serdang District Attorney's Office, Labuhan Deli - Ruth Herlina Simorangkir; Cut Fitri Rostina; Fauzi, Fauzi (Cita konsultindo, 2025)
This study aims to analyze the influence of the work environment and work discipline on employee performance at the Deli Serdang District Attorney's Office Branch in Labuhan Deli. The research adopts a quantitative approach, utilizing surveys and structured questionnaires to collect data from employees. The work environment and work discipline are evaluated as independent variables, while employee performance serves as the dependent variable. By employing statistical analysis, this study examines the significance and strength of the relationship between these factors. The findings contribute to the understanding of how organizational conditions and individual discipline can enhance employee effectiveness. Additionally, this study highlights practical implications for improving workplace management and employee productivity.